2015
DOI: 10.1039/c4ay02725f
|View full text |Cite
|
Sign up to set email alerts
|

SERS detection of expired tetracycline hydrochloride with an optical fiber nano-probe

Abstract: This paper was to develop a Raman spectra analytical method for the analysis of tetracycline hydrochloride. The surface enhanced Raman spectroscopy (SERS) were measured with the optical fiber nano-probe coated nanoparticles. Both the normal and the expired tetracycline hydrochloride were analyzed by the direct detection mode and remote detection mode. The results showed that the surface-enhanced Raman spectra could provide the chemical information for distinguishing the normal drugs from the expired ones. It d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…2a, a set of more pronounced peaks appear in the TET spiked milk at 1280 cm −1 , 1322 cm −1 and 1621 cm −1 . This evidence is in accordance with the TET characteristic peaks reported in the literature 6,35 although with a small shift, due to the interaction of the TET with the milk matrix. The peak at 1280 cm −1 is correlated to bending modes of C-H in the positions 4, 4a, 5, 5a, O-H12 and amid-NH and to stretching modes of C10, 3-O, C-H7, 8, 9, C4a-C5 and amid-NC.…”
Section: Resultssupporting
confidence: 92%
“…2a, a set of more pronounced peaks appear in the TET spiked milk at 1280 cm −1 , 1322 cm −1 and 1621 cm −1 . This evidence is in accordance with the TET characteristic peaks reported in the literature 6,35 although with a small shift, due to the interaction of the TET with the milk matrix. The peak at 1280 cm −1 is correlated to bending modes of C-H in the positions 4, 4a, 5, 5a, O-H12 and amid-NH and to stretching modes of C10, 3-O, C-H7, 8, 9, C4a-C5 and amid-NC.…”
Section: Resultssupporting
confidence: 92%
“…Although most of the applications are focused on planar substrates for Lab-On-a-Chip (LOC) applications [95,96], optical fiber approaches have been also reported using nanoparticle decorated tapered optical fibers [94,[97][98][99][100]. Another example can be found in [94] where it is reported that silver nanoplates were deposited on the tapered surface of an optical fiber with the LbL technology (Figure 8).…”
Section: Surface-enhanced Raman Spectroscopy (Sers)mentioning
confidence: 99%
“…Surface enhanced raman scattering (SERS) is a non-destructive and powerful tool that not only offers high specificity and sufficient structural information of chemical and biological molecules [1]- [3], but also provides enormous enhancement for the SERS effect, making it suitable for applications in trace analysis, environmental monitoring, biochemical sensing, and food safety, etc [4]- [6]. Due to the enhancement of electromagnetic fields around metal nanostructures (typically silver and gold), the Raman signal of analyte molecules in the immediate vicinity of the nanostructures could be increase drastically by about orders of 10 6 or even more [7], [8].…”
Section: Introductionmentioning
confidence: 99%